FINANCIAL PERFORMANCE ANALYSIS OF INDONESIAN TELECOMMUNICATION COMPANY - Setiawan, Eko Agus (PT. Arsil Reka Engineering, 2024)
This study thoroughly examines the financial performance of four leading telecommunications companies in Indonesia. Telkom Indonesia (TLKM), XL Axiata (EXCL), Smartfren (FREN), and Indosat (ISAT) over the period 2021–2022. By analysing financial performance using financial ratios such as leverage ratio (DAR, DER) and profitability (NPM, ROA, ROE), it can be seen that Telkom Indonesia experienced a decrease in debt ratio and a decrease in profitability. XL Axiata saw an improvement in its debt ratio but also experienced a considerable decline in profit. Smartfren showed a decrease in its debt ratio and a significant increase in profitability. Indosat had a combination of changes in profitability and a decrease in debt ratio. These findings emphasise the importance of organisations prioritising efficient debt management and strategic initiatives to improve profitability in the changing telecommunications sector.